SiRNA-Conjugated Nanoparticles to Treat Ovarian Cancer. (April 2019) - Halbur, Christopher; Choudhury, Niharika; Chen, Michael; Kim, Jun Hyuk; Chung, Eun Ji
Ovarian cancer is the fifth-most lethal cancer among women due to a lack of early detection and late-stage treatment options, and it is responsible for more than 14, 000 deaths each year in the United States. Recently, there have been advances in RNA interference therapy, specifically with small interfering RNA (siRNA), to reduce tumor burden for ovarian cancer via gene down-regulation. However, delivery of siRNA poses its own challenges, as siRNA is unstable in circulation, is unable to be effectively internalized by cells, and may cause toxicity in off-target sites. To address such challenges, nanoparticle carriers have emerged as delivery platforms for the biocompatible, targeted delivery of siRNA-based therapies. Several preclinical studies have shown the promising effects of siRNA therapy to reduce chemotherapy resistance and proliferation of ovarian cancer cells. This review evaluates the recent advances, clinical applications, and future potential of nanoparticle-mediated delivery of siRNA therapeutics to target genes implicated in ovarian cancer.